Cultural Representations in Indonesian EFL Textbooks: A Synthesis Study - Dyah Mustikareni (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study aims to synthesize findings from eight qualitative research articles examining the representation of cultural content in English as a Foreign Language (EFL) textbooks used in Indonesia. The research is motivated by the increasing emphasis on intercultural competence in language education and the need to align textbook content with national character education and global communication goals. Although EFL textbooks are widely used in Indonesian classrooms as primary instructional materials, concerns have emerged regarding their cultural relevance and inclusivity. A thematic synthesis method was employed to analyze the selected studies, which focused on textbooks published or used in Indonesia between 2016 and 2025. The analysis consisted of three stages: coding primary findings, clustering them into descriptive themes, and synthesizing cross-study analytic themes. The findings reveal four major themes: the dominance of target cultures, superficial representation of cultural and multicultural values, cultural imbalance and bias, and the limited application of intercultural approaches. While some locally developed textbooks introduce Indonesian cultural content, they often fail to support deeper intercultural reflection and engagement. This study concludes that Indonesian English as a Foreign Language (EFL) textbooks need to be more culturally balanced and pedagogically reflective. Integrating intercultural competence into textbook design can better support learners’ linguistic development, national identity formation, and the development of global citizenship. The results necessitate a critical evaluation and revision of textbook content to ensure alignment with both national educational policies and intercultural communication objectives.